ANALISIS PENGULANGAN RADIOGRAFI PERIAPICAL DI INSTALASI RS PKU MUHAMMADIYAH KOTA YOGYAKARTA - Muhammad Ivande Gibran Saputra,; Annisa Nur Istiqomah,; Muhamad Faik, (Journal of Innovation Research and Knowledge, 2025)
Periapical radiography is essential for comprehensively assessing the condition of teeth and supporting tissues. However, suboptimal image quality often leads to retakes, which increase radiation dose and reduce service efficiency. Based on preliminary observations, the retake rate of periapical radiographs at the Radiology Department of PKU Muhammadiyah Hospital Yogyakarta City was relatively high and had not been analyzed between August and October 2024. According to Ministry of Health Decree No. 129/Menkes/SK/II/2008, the acceptable retake limit is ≤2%. This study aims to identify the factors causing periapical radiograph retakes, calculate the retake percentage, and evaluate radiographers’ understanding of the criteria for optimal image quality. Method: This study employed a mixed-method design. Data were collected through direct observation, interviews, questionnaires, and documentation of radiograph retake records from August to October 2024 at the Radiology Department of PKU Muhammadiyah Hospital Yogyakarta City. The research subjects consisted of 3 radiographers for interviews and 10 radiographers for questionnaires, focusing on the percentage of retakes, contributing factors, and their understanding of periapical dental image quality criteria. Data were analyzed by calculating the retake rate and frequency distribution by cause category, as well as assessing radiographers’ knowledge of the criteria for producing accurate periapical dental images. Results: Out of 269 examinations, 51 periapical radiograph retakes were recorded (18.95%), exceeding the limit set by Decree No. 129/2008 (≤2%). The main cause was film positioning errors (60.78%), while equipment errors were the least frequent factor (3.92%). Although 60% of radiographers demonstrated strong theoretical knowledge, 50% showed strong practical skills, and 70% were able to evaluate optimal images, inconsistencies between theory and practice remained. Efforts to reduce retakes included patient education and the implementation of periodic retake analysis programs. Conclusion: The high retake rate indicates the need for improvements in technical and procedural aspects, patient education, equipment calibration, refresher training, optimization of supporting tools, and regular repeat analysis evaluations to enhance accuracy and minimize retakes